CYBERBULLYING RELATIONSHIP WITH SELF-ESTEEM, SOCIAL DEVELOPMENT AND MENTAL WELL-BEING OF UNDERGRADUATE STUDENTS IN A FEDERAL UNIVERSITY IN ANAMBRA STATE, NIGERIA - Elizabeth Ifeoma Anierobi; Chioma Christiana Akuneme; Gloria Uzoamaka Nnaemeka (Social Sciences and Education Research Review)
Most undergraduate students have been reported to have experienced cyberbullying; and the effects that cyberbullying has on its victims could be quite subtle and deleterious. This study aims to investigate the relationship that cyberbullying has with the self-esteem, social development, and mental well-being of students in a federal university in Anambra State. The rationale is based on the increasing impacts of cyberbullying on students. The correlation research design was used for the study. The sample size consisted of 216 undergraduate students. Cyberbullying Scale (CbS), Self-esteem Scale (SES), Social Development Scale (SDS), and Mental Well-Being Scale (MWbS) were used for eliciting responses from the respondents. Cronbach Alpha was used in determining the reliability of the instruments which yielded alpha coefficients of .74 for CbS, .788 for SES, .847 for SDS and .823 for MWbS. Multiple correlations and linear regression analyses were used in the analysis of the data with the SPSS statistical software program. The findings revealed that cyber bullying has a significant relationship with university students' self-esteem and social development. There was no significant relationship between cyberbullying and mental wellbeing of university students. It was concluded that cyberbullying may be a critical factor that can impact aspects of students' psychosocial development such as their self-esteem, social development, and mental wellbeing. Implications of the study were highlighted.